2018
DOI: 10.1097/wno.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

Acute Management of Optic Neuritis: An Evolving Paradigm

Abstract: The current management of acute optic neuritis (ON) is focused on expediting visual recovery through the use of high-dose intravenous corticosteroids. The recent identification of specific autoantibodies associated with central nervous system inflammatory disorders has provided novel insights into immune targets and mechanisms that impact the prognosis, treatment, and recurrence of ON. Therefore, neurologists and ophthalmologists need to be aware of clinical, laboratory, and imaging findings that may provide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…Based on the results obtained, we propose a possible therapeutic strategy for patients with undiagnosed ON, as shown in Figure 3 . Before deciding to administer high-dose IVMP pulse therapy to patients suspected of ON, clinicians should exclude the possibility of infectious ON (e.g., syphilitic ON with HIV infection, Lyme ON, and tuberculous ON) because IVMP monotherapy without antibiotics may aggravate disease activity in such conditions ( 8 , 48 50 ). Although the incidence of infectious ON is much lower than that of ON of other noninfectious inflammatory causes, a comprehensive examination including medical history taking, fundoscopy, imaging, and blood testing is required to correctly differentiate infectious ON before deciding on the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results obtained, we propose a possible therapeutic strategy for patients with undiagnosed ON, as shown in Figure 3 . Before deciding to administer high-dose IVMP pulse therapy to patients suspected of ON, clinicians should exclude the possibility of infectious ON (e.g., syphilitic ON with HIV infection, Lyme ON, and tuberculous ON) because IVMP monotherapy without antibiotics may aggravate disease activity in such conditions ( 8 , 48 50 ). Although the incidence of infectious ON is much lower than that of ON of other noninfectious inflammatory causes, a comprehensive examination including medical history taking, fundoscopy, imaging, and blood testing is required to correctly differentiate infectious ON before deciding on the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with NMOSD typically present with repeated attacks of optic neuritis (ON) and/or myelitis (3,4), and are likely to relapse without proper relapse prevention treatments, acquiring neurological disabilities accumulated in a stepwise manner (5)(6)(7). In the acute phase of attacks in NMOSD, immune suppression with high-dose intravenous methylprednisolone (IVMP) pulse therapy with or without oral tapering is the gold standard treatment at present (8)(9)(10)(11)(12). In addition to IVMP, plasma exchange (PLEX) and intravenous immunoglobulin (IVIg) therapy are also known to be effective for treating acute NMO exacerbations and preventing relapse (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The most common approach to acute relapse management is immediate initiation of high-dose corticosteroids (intravenous methylprednisolone 1000 mg daily for 3–5 days), with a slow taper (i.e., oral prednisone starting at 1 mg/kg/d with a reduction of 5 mg every 2 weeks) to ameliorate neurological impairment [ 1 , 9 16 ]. Yet, studies have shown that long-term outcomes from NMOSD relapses may correlate more robustly with the severity of attacks at presentation than treatment timing (within 14 days from symptom onset or later) [ 13 ].…”
Section: Acute Relapse Managementmentioning
confidence: 99%
“…Typical ON is a condition occurring in 1.5-5.1 cases per 100,000 with a higher incidence in females, whereas NMO and MOGAD are 0.5-1.4 per 100,000 persons [2][3][4]. NMO, a variant of NMO spectrum disorder (NMOSD), and MOGAD are characterized by serological positivity to aquaporin-4 (AQP-4) antibody and MOG antibody for NMO/NMOSD and MOGAD, respectively, but the frequency of double seropositivity has rarely been reported [5][6][7].…”
Section: Introductionmentioning
confidence: 99%